Estrategias y reacomodos de las masculinidades en un entorno fronterizo - Pacheco González, Sergio (Editora CRV, 2019)
https://www.editoracrv.com.br/produtos/detalhes/34495-estrategias-y-reacomodos-de-las-masculinidades-en-un-entorno-fronterizo